Is Silodosin a Better Alternative to Tamsulosin as a Part of Medical Expulsion Therapy in Patients with Lower Uretic Calculi? - Sajid Iqbal, Muhammad Sohail, Ijaz Ur Rehman, Farooq Malik, (Pakistan Journal of Medical & Health Sciences, 2023)
Background: Urinary stones are one of the most common illness of the urinary tract. Medical expulsion therapy (MET) is the non-invasive surgery option for patients with small urinary stones. Tamsulosin is a selective alpha-1A adrenergic receptor blocker. Silodosin is lately investigated as an alpha-1A adrenoceptor blocker. Study design: It is a randomized controlled study conducted at Department of Urology, Civil Hospital, Mirpur Khas and Sir Ganga Ram Hospital, Lahore for the duration of six months from July 2022 to December 2022. Material and Methods: The data was taken from 85 patients who were suffering from lower uretic calculi with 45 patients who received prescription of silodosin (8mg) and 40 patients who were given daily dose of tamsulosin (0.4mg) for treatment. The dose was given to patients over duration of 28 days. Results: The mean BMI of patients was 25.5 kg/m2 for group A patients and 27.5 kg/m2 for group B patients. Average Hounsfield unit was 57.9±2.1 and 58.6±1.3 (HU/mm) for group A and B respectively. Most of the patients (n=62) had stone size greater than 5mm. The expulsion rate in patients with stone size greater than 5mm was found as 82.1% and 65.2% in group A and B respectively. Conclusion: The study concludes that there is a better and more significant control of pain shown by silodosin as it increases the rate of expulsion more significantly as compared to tamsulosin. The requirement of analgesics by silodosin group patients was also less and therefore it can be a better alternative to tamsulosin for the treatment of lower uretic calculi. Keywords: Tamsulosin, silodosin and medical expulsion therapy.